2013
DOI: 10.1155/2013/262796
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Shikonin Stimulates Epithelial-Mesenchymal Transition (EMT) in Skin Wound Healing

Abstract: Although various pharmacological activities of the shikonins have been documented, understanding the hierarchical regulation of these diverse bioactivities at the genome level is unsubstantiated. In this study, through cross examination between transcriptome and microRNA array analyses, we predicted that topical treatment of shikonin in vivo affects epithelial-mesenchymal transition (EMT) and the expression of related microRNAs, including 200a, 200b, 200c, 141, 205, and 429 microRNAs, in mouse skin tissues. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…The red pigments from the roots of L. erythrorhizon have been used since ancient times as dyestuffs for fabrics, cosmetics and food (Chang et al 2008), and as crude drugs for anti-inflammatory ointment (Ito et al 2011). It exhibits biological activities such as wound healing (Yin et al 2013), antioxidant (Weng et al 2000), antifungal and antitumour (Han et al 2008;Yang et al 2009;Lu et al 2011;Andujar et al 2013). Previous phytochemical studies reported that the red pigments of L. erythrorhizon were mainly composed of naphthoquinone compounds, such as b-hydroxyisovalerylshikonin, acetylshikonin (Gwon et al 2012), propionylshikonin (Cho et al 1999), isobutyrylshikonin (Syklowska-Baranek et al 2012), b,b-dimethylacryloylshikonin (Li et al 2012, isovalerylshikonin, isobutyrylshikonin (Zhao et al 2011) and a-methylbutyrylshikonin.…”
Section: Introductionmentioning
confidence: 99%
“…The red pigments from the roots of L. erythrorhizon have been used since ancient times as dyestuffs for fabrics, cosmetics and food (Chang et al 2008), and as crude drugs for anti-inflammatory ointment (Ito et al 2011). It exhibits biological activities such as wound healing (Yin et al 2013), antioxidant (Weng et al 2000), antifungal and antitumour (Han et al 2008;Yang et al 2009;Lu et al 2011;Andujar et al 2013). Previous phytochemical studies reported that the red pigments of L. erythrorhizon were mainly composed of naphthoquinone compounds, such as b-hydroxyisovalerylshikonin, acetylshikonin (Gwon et al 2012), propionylshikonin (Cho et al 1999), isobutyrylshikonin (Syklowska-Baranek et al 2012), b,b-dimethylacryloylshikonin (Li et al 2012, isovalerylshikonin, isobutyrylshikonin (Zhao et al 2011) and a-methylbutyrylshikonin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we also observed that topical treatment of mouse skin with SK conferred a potent stimulatory effect on EMT activity and effectively suppressed the expression of associated microRNAs (200 family microRNAs) during the subsequent skin wound-healing activity [5] . In normal somatic tissues, epithelial-to-mesenchymal transition (EMT) activity is not only instrumental in facilitating wound-healing activity but also in promoting tissue fibrosis [30][31][32] .…”
Section: A Selected Therapeutic Approach May Be Needed For Applicatiomentioning
confidence: 98%
“…On the other hand, topical treatment with SK was found to also confer a potent stimulatory effect on EMT and many pro-inflammatory activities, such as the increase in expression of MMP2, MMP-9 and vimentin, during wound-healing of skin tissues [5] . These results indicate that SK may exhibit both pro-and anti-inflammatory activities at the tissue/organ levels.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations